2016
DOI: 10.1080/09853111.2016.1265398
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Pleistocene travertine depositional system from terraced slope to fissure-ridge in a mixed travertine-alluvial succession (Jebel El Mida, Gafsa, southern Tunisia)

Abstract: The Quaternary stratigraphic record of Jebel El Mida, composed of continental deposits, is a useful example of concomitant travertines and alluvial deposition in an extensional setting. Travertine deposition occurred in a faulted Pleistocene alluvial fan giving rise to seven (recognised) facies interfingering with five other alluvial ones. The travertine depositional events indicate a tectonically driven evolution from terraced slope (facies group FC1–FC6) to a travertine fissure ridge-type depositing phase (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 59 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…If siloxanes are present in the sample, the 1110–1000 cm −1 band is masked by strong Si–O–Si absorption, as indicated by the arrows ( Figure 3 ). Comparing the FTIR images of the same stone, treated limestone, with different coupling agents, 3-MPTMS and CoatOSil T-Cure, we noticed variation values, indicating the presence of Si–O–Si around values between 1130 and 1050 cm −1 , and it seems that 3-MPTMS is more reactive, and thus, the intensity of these peaks was stronger on both stone samples [ 45 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…If siloxanes are present in the sample, the 1110–1000 cm −1 band is masked by strong Si–O–Si absorption, as indicated by the arrows ( Figure 3 ). Comparing the FTIR images of the same stone, treated limestone, with different coupling agents, 3-MPTMS and CoatOSil T-Cure, we noticed variation values, indicating the presence of Si–O–Si around values between 1130 and 1050 cm −1 , and it seems that 3-MPTMS is more reactive, and thus, the intensity of these peaks was stronger on both stone samples [ 45 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 93%
“…Siloxanes with thiolic moieties were chosen as silanization agents, since it is known that silver nanoparticles have a high affinity to the thiol group [ 30 , 31 ]. These thiol groups attach to the AgNPs via coordinative covalent bonding; thus, the nanoparticles are anchored to the mineral substrate, facilitating and changing its various properties [ 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral interaction between different depositional environments are commonly observed phenomena in continental carbonate studies, however, it is more often reported in the case of intercalation with terrigenous sediments (e.g. Croci et al, 2016;Huerta et al, 2016;Henchiri et al, 2017;Verbiest et al, in press). A unique depositional system, however, has been described from the Lake Urmia (NW Iran)…”
Section: Cukor Fissure Ridgementioning
confidence: 99%
“…1995; Lu et al, 2000;Central Italy: Capezzuoli et al, 2014;Della Porta, 2015;Croci et al, 2016;Della Porta et al, 2017;Violante et al, 1994aViolante et al, , 1994b; (Chafetz and Folk, 1984;Riding, 1998: D'Argenio et al 1981;Scheuer and Schweitzer, 1981;Altunel and Hancock, 1993a;Khatib et al 2014;Lebatard et al, 2014;Claes et al, 2015;Henchiri et al, 2017;Liu et al, 1995;Lu et al, 2000;Pentecost, 2005 for a review; Capezzuoli et al, 2014, Della Porta, 2015Croci et al, 2016;Della Porta et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%